2018
DOI: 10.1017/s0007114518001721
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Hb concentration and risk of preterm birth in over 2·7 million Chinese women aged 20–49 years: a population-based cohort study

Abstract: Evidence on the association between maternal Hb concentration and preterm birth (PTB) risk is inconclusive. This paper aimed to explore whether women with anaemia or high Hb level before pregnancy would be at higher risk of PTB. We conducted a population-based cohort study with 2 722 274 women aged 20-49 years, who participated in National Free Pre-Pregnancy Checkups Project between 2013 and 2015 and delivered a singleton before 2016 in rural China. Logistic models were used to estimate OR and 95 % CI after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…In total, 272 studies were included in our review and 95 studies met the criteria for inclusion in the meta‐analyses (Fig. ), while the remaining 177 studies are summarized in table format only. A summary of all studies included in the meta‐analyses is provided in Table S2 (online only).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 272 studies were included in our review and 95 studies met the criteria for inclusion in the meta‐analyses (Fig. ), while the remaining 177 studies are summarized in table format only. A summary of all studies included in the meta‐analyses is provided in Table S2 (online only).…”
Section: Resultsmentioning
confidence: 99%
“…measured Hb concentrations a median of 5 weeks prior to conception, 1.5 months prior to conception, and on or before the first day of the last menstrual cycle, respectively, while the preconception timing for Maghsoudlou et al . is unclear (1 year before pregnancy) …”
Section: Resultsmentioning
confidence: 99%
“…This issue is more common in low-income countries, especially in Central and West Africa (48 %) and in South Asia (47 %) (32) . Previous studies have shown that maternal anaemia, especially severe anaemia, can be associated with an increased risk of low birth weight (33,34) , preterm birth (23,35) and smallfor-gestational-age (36) . However, there were only two studies that have assessed the association between maternal anaemia and SA risk.…”
Section: Discussionmentioning
confidence: 99%
“…A large population-based retrospective cohort study among reproductive-aged (20-49 years) women was conducted based on National Free Pre-pregnancy Check-up Project (NFPCP), which was supported by the National Health Commission and Ministry of Finance of the People's Republic of China, with the purpose to provide free preconception health examinations and follow-up of pregnancy outcomes for reproductive-aged couples who planned to get pregnant within the next 6 months. Published articles detailing the project-related design, organisation and implementation can be found elsewhere (10,23,24) . The current study was conducted according to the guidelines laid down in the Declaration of Helsinki, and all procedures involving humans were approved by the Institutional Research Review Board at the National Research Institute for Health and Family Planning.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation